Influence of environmental factors on the occurrence of Ixodes ricinus ticks in the urban locality of Brno - Pisarky, Czech Republic - Žákovská, Alena; Netušil, Jakub; Martiníková, Hana (Journal of vector ecology, 2007)
The occurrence of Ixodes ricinus ticks was observed in the suburban locality of Brno-Pisarky (South Moravia, Czech Republic) from March to November, 1996 to 2002. A total of 2,813 ticks was collected. Statistical tests divided the activity of ticks into three periods during the year. The curve of seasonality had two peaks with a maximum in May and August, with a significantly larger number of specimens collected during this period compared to other months. The abundance of ticks during Spring and Autumn months was comparable. All developmental stadia of ticks were found in this locality. The number of larvae, males, and females was not significantly different, but the occurrence of nymphs was significantly greater. Except for the year 2000, there were no statistically significant differences in tick abundance. Tick activity was not dependent on humidity but did vary directly with temperature. This relation had a linear character and could be described by the equation y = 8.3 + 1.8x.
Keywords: larva; Climate; Ecology; podnebí; Larva; Ixodes; zvířata; Nymph; Czech Republic; roční období; Financing, Organized; financování organizované; nymfa; vlhkost; mužské pohlaví; Česká republika; klíště; Seasons; ženské pohlaví; Female; Animals; Male; ekologie; Humidity